THE CONNECTED CAR: IOT-BASED SMART SYSTEMS FOR CARS. - NAIDU, THALAPANENI PENCHALA; BHARGAV, TOLETI VEERAVENKATA MANIKANTHA; VISHNU, MAKHAM SAI; KEERTHI, UPPALAPATI; VARSHITHA, TADEPALLI; PREETHAM, C. SREENIVAS; AHAMMAD, S. K. HASANE; SAIKUMAR, K. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Travelling has changed a lot through the ages. The present trends are focused on more than just locomotion. The experience is the key to a happy and comfortable ride. We have emerged in multiple ways to better the car experience. Along with all the latest hi-tech innovation and supreme luxury, the importance of safety, security and user-friendly features has seen a steep rise. People are now more aware of how safety and security are principal for a vehicle. In this project we are aiming to build a solution which can address three major areas namely, Safety, Security and Ease of Access. In each of these areas we want to device a way to make the user experience better and keep it economic as much possible. We are using microcontrollers and sensors to build this system. We are using the Arduino platform. Vehicle support systems are increasing in innovation and technology and are making the user experience better. This project is an attempt to bring about such systems on to a single platform and make it easier for control, administration, and safety.